Aspect of tree for controlling outdoor microclimate: a case study in IIUM - Mohd Nordin, Mohamad Nur Ridhwan; Mad Nafiah, Mohd Nasrul Nafizie; Abu Bakar, Aniza; Mohamad, Amira Nadhirah (2014)
Trees have been known for their potential in controlling the microclimate. Trees can be differentiated based on species and their physical aspect or character. This aspect has certain influence in the screening potential of trees on solar radiation from reaching the ground. Identifying the characteristic of tree capable in controlling the environmental problem at most is going to be the choice in designing outdoor landscape with green element inside of it. Tree functioning to mitigate environmental problem is highly needed to improve the air quality and make a proper shelter to protect from direct sunlight heat. Understanding the tree is difficult as tree even between the same species have their own variable strength level that is able to influence changes to the environment microclimate. Many factors needed to be concern regarding the health of trees, shape, and size and planting method required to make an effective impact. Other factors that will be also considered are wind speed, wind direction, air temperature and relative air humidity in order to precisely describe the actual site microclimate qualities. Observation and data collection in this study can help appropriately assess the environmental benefits provided by green trees and useful inputs in designing landscape spaces to attain the result for sustainable design. This paper will suggest the crucial aspect of tree that able to control outdoor microclimate as future design guideline in proposing a park design.